Efficient remediation of 17α-ethinylestradiol by Lentinula edodes (shiitake) laccase. (April 2017) - Eldridge, Hannah C.; Milliken, Alexander; Farmer, Charlene; Hampton, Ar'Shundra; Wendland, Nils; Coward, Lori; Gregory, Denise J.; Johnson, Corey M.
Abstract: Removal of the endocrine disrupting chemicals (EDCs) which commonly pollute wastewater has been observed upon incubation with white-rot fungi. To date, there is no consensus on what is the optimal fungal source for the enzymes that catalyze remediation of EDCs. Herein, two white-rot fungi cultures ( Lentinula edodes and Phanerochaete chrysosporium ) were tested for an ability to remove the pollutant 17α-ethinylestradiol (EE2). Mass spectrometry indicates a moderate removal of EE2 for simple potato dextrose cultures of both fungi within one week (50% EE2 remaining in L. edodes ; 57% remaining in P. chrysosporium ). Due to an absence of measured laccase activity from P. chrysosporium, it was hypothesized that the improved EE2 remediation in L. edodes was due to laccase. Supplementation of L. edodes cultures that improve production of laccase exhibit a corresponding increased ability to remove EE2 (20% EE2 remaining). P. chrysosporium cultures did not respond to supplementation accordingly (48% remaining). Consistent with laccase-specific remediation by L. edodes, incubations of EE2 in the presence of a purified laccase produced identical mass spectra to those observed from L. edodes cultures. The dominant soluble product observed for each has a mass consistent with hydroxylated EE2 ( m/z 313). To our knowledge, this is the first demonstration of EE2 remediation by L. edodes culture. In addition, data indicate that the removal of EE2 is improved by increased production of the high-activity laccase secreted by the fungus. Graphical abstract: Highlights: For the first time, we demonstrate the ability of Lentinula edodes cultures to remove the pollutant, 17α-ethinylestradiol. L. edodes is identified as an efficient source of high-activity laccase useful in this bioremediation application. L. edodes cultures with improved laccase production display an increased ability to remove 17α-ethinylestradiol. The metabolites of EE2 oxidation in the presence of purified laccase are identical to those produced in L. edodes cultures.